The process of environmental management in Cuba. Proposal and implementation of its national and regional methodological procedure - Cárdenas López, Obllurys; Mateo Rodríguez, Juan Manuel; Martínez Suárez, Juan Mario (Geographicalia, 2015)
The necessary interaction between land use and the environment management was enacted in Law 81 and the National Environmental Strategies (EAN) since 1997, in Cuba. Several situations slowed its completion, the lack of methodological procedures that will guide the process, was one of them so the EAN of 2011-2015 and the Guidelines of the PCC, in the year 2011, ratify it as objective. In addressing this issue and the inclusion of the results of studies of hazard, vulnerability and risk and climate change scenarios currently lies of the present investigation. Given the hypothesis that: the use of inclusive and participative methodological procedures will facilitate modeling of environmental management (MOA) to provide regulations, guidelines and environmental standards to land use planning process; main objective is pursued: to propose methodological procedures for the development of the MOA and perform validation at national and municipal levels. Employees are combined theoretical and empirical methods in the development of procedures and their validation at different scales. It was concluded in the relevance of using the proposed procedures for the preparation of the MOA, taking as a basis the participatory approach and the landscape units, as units of analysis.